2004
DOI: 10.1192/bjp.184.2.118
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of antisocial personality

Abstract: Childhood disruptive behaviour has powerful long-term effects on adult antisocial outcomes, which continue into middle adulthood. The importance of number of symptoms, the presence of disruptive disorder, and intermediate experiences highlight three areas where interventions might be targeted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(54 citation statements)
references
References 25 publications
3
45
0
6
Order By: Relevance
“…The previously established associations between criminal behaviour and antisocial personality disorder in adulthood and childhood precursors of both conduct disorder (Robins, 1966(Robins, , 1978Loeber, 1990) and hyperactivity (Farrington et al, 1990;Simonoff et al, 2004) were confirmed by our findings. However, the strength of association between childhood hyperactivity and adult antisocial traits was weaker than that of conduct disorder, suggesting either that hyperactivity could evolve into different conditions in adulthood, for example, substance abuse or other personality disorders, or simply that the risks for persisting antisocial behaviour in adulthood were not as strong as for conduct disorder.…”
Section: Tablesupporting
confidence: 80%
“…The previously established associations between criminal behaviour and antisocial personality disorder in adulthood and childhood precursors of both conduct disorder (Robins, 1966(Robins, , 1978Loeber, 1990) and hyperactivity (Farrington et al, 1990;Simonoff et al, 2004) were confirmed by our findings. However, the strength of association between childhood hyperactivity and adult antisocial traits was weaker than that of conduct disorder, suggesting either that hyperactivity could evolve into different conditions in adulthood, for example, substance abuse or other personality disorders, or simply that the risks for persisting antisocial behaviour in adulthood were not as strong as for conduct disorder.…”
Section: Tablesupporting
confidence: 80%
“…The strongest contribution from a single diagnosis was found for Conduct Disorder (CD), which only rarely appeared without other co-morbid diagnoses and problems. Similar findings were obtained in a twin study of childhood hyperactivity and conduct problems as potential predictors of Antisocial Personality Disorder and crime in adulthood [7] and in a Norwegian longitudinal study of former CAP patients [27].…”
Section: Discussionsupporting
confidence: 82%
“…It should be noted that two child psychiatric diagnoses characterized by externalizing symptoms share descriptive features with the LCP pattern: Attention Deficit Hyperactivity Disorder (ADHD) and Conduct Disorder (CD) [5]. Externalizing symptoms in childhood appear to belong to a higher order factor [5], are associated with a range of negative clinical outcomes in adulthood and tend to persist over the life course [6] [7].…”
Section: Introductionmentioning
confidence: 99%
“…While some studies do show that positive symptoms are associated with aggressive behaviour even after taking account of CD, the existing evidence indicates that those with CD are not distinguished from other patients with schizophrenia by symptom profiles (Moran & Hodgins 2004). Based on a comparison of the results of a small number of studies, the strength of the association between CD in childhood and violence in adulthood appears to be similar among individuals who develop schizophrenia (Hodgins et al 2005Swanson et al 2006) as it is among those who do not (Siminoff et al 2004;Loeber et al 2005). In addition, the number of CD symptoms prior to age 15 is linearly associated with the development of antisocial personality disorder in adulthood among persons with schizophrenia, as it is in the general population (Robins et al 1991).…”
Section: Early Start Offenders With Schizophreniamentioning
confidence: 99%